DETECTION OF PVY (POTATO Y POTYVIRUS), ON POTATO CULTIVARS USING BIOLOGICAL AND MOLECULAR METHODS GROWING IN SOUTH-WEST TURKEY - N. Yardımci; H. Çulal Kılıç; T. Özdemir (Journal of Animal and Plant Sciences, 2014)
A large number of pathogens, cause economically important diseases on potato plants worldwide. Among these pathogens, potato virus Y potyvirus is one of the most common pathogens of potato. In this study, observations of mosaic patterns on leaves, stunting of the plant, leaf malformations, on potato plants in this region during field surveys indicated the presence of PVY in South-West region in Turkey. To test the presence of this virus in potato fields, leaf samples were collected from different areas in the region. In total 54 (52 potato and 2 N. glutinosa ) samples were first tested by reverse transcriptase-polymerase chain reaction (RT-PCR) assay using primers specific to coat protein gene of PYV. As a result of RT-PCR, 23 potato leaf samples (44.23 %) were determined as positive. RT-PCR positive some of the samples were then used in biological studies.
Keywords: PVY; Potato; RT-PCR; Molecular characterization